PENGARUH INTENSITAS GAME ONLINE TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN EKONOMI LINTAS MINAT KELAS XI IA DI SMA NEGERI 5 PEKANBARU - Magdalena Purwasih; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the influence of the intensity of the game online against the learning achievements on economic subjects of cross-class XI IA interest in SMA Negeri 5 Pekanbaru. The entire research population of students who attend a cross-economy interests as much as 196 students and as a sample research amounted to 45 students obtained from pre surve. This is done by sampling technique of purposive sampling quota. The data collected via the question form and documentation. The results showed: (1) the learning achievements of students still low average acquisition value 77.75 with KKM amounting to 80. (2) the frequency of different types of online games are most popular among students of non economic online game, online games, online games and competitions is playing a non online game economics with the highest percent of number 26 and the percentage of 57.8%, based on the highest online game classification i.e. mobile legend with the average number of 2.37. Economic online game for the number of tentinggi of 3 percent with a percentage amounting to 6.7, with the highest economic online game classification i.e., railroad tycoon II with an average number of 1.67. While online gaming competition number of the highest numbered 16 percent and the percentage of 35.5%, with the highest online game competitions classification i.e. mobile legend with the average number of 2.18. (3) research results based on multiple linear regression equation PB = 0.357 87.451 – GONE – 0.486 GOE – 0.287 KGO meaning non economic online game, online games, online game and competition have a negative significant influence towards the achievement learn. This occurs because students tend to have high intensity against online gaming and online gaming competition rather than economic online game.Key Words: Intensity game online, Student Achievements